Assessing the safety of schools affected by geo-hydrologic hazards: The geohazard safety classification (GSC). (March 2016) - Pazzi, Veronica; Morelli, Stefano; Pratesi, Fabio; Sodi, Thalita; Valori, Luca; Gambacciani, Luca; Casagli, Nicola
Abstract: Three-quarters of the world population suffered natural disasters at least once between 1980 and 2000. Furthermore, last years' chronicles showed us several geological events that repededly affected urban landscapes. As a consequence beside the loss of human lives and environmental degradation, lots of students were excluded from school, many of whom never to return. Natural hazards have physical, educational, economic and psychosocial impacts. Nowadays it is well ascertained that to decrease this impact by means of structural interventions requires considerable economic resources. Nevertheless, the comparision consequences of similar events in different contexts, it emerges that risk awareness of the population and education to emergency procedures have a positive impact on the occurrence of victims. It follows that the ability of school occupants exposed to hazards to resist and recover from the effects of a hazard in a timely and efficient manner plays a key role to reduce risk, moreover resulting in a cheaper and faster strategy of intervention.This paper presents a new cost-effective methodology and procedure to rapidly assess the geohazard safety classification (GSC) of schools and provides useful information to local decision makers. The GSC, based on the concepts of hazard, vulnerability and resilience, can be calculated integrating ancillary data by means of rapid and not invasive field surveys and questionnaires distributed to the schools employees. Moreover, it can be easily read and understand since it uses the same type of scale as energy efficiency, to indicate the occupants' safety in case of adverse events related to geo-hydrologic hazards.This new rapid assessment methodology have been tested on 10 schools in Tuscany (Italy) and the present paper shows how the GSC can be strongly affected by the lack of ancillary information or the incompleteness of the Risk Assessment Document as well as the school occupants poor perception of geo-hydrologic risk. However, this limitation is at the same time one of the strengths of the GSC: investing in education is a cost-effective way to increase substantially the GSC. Graphical abstract: